2005
DOI: 10.1104/pp.104.051839
|View full text |Cite
|
Sign up to set email alerts
|

Possible Roles for Mannitol and Mannitol Dehydrogenase in the Biotrophic Plant PathogenUromyces fabae 

Abstract: Levels of the C6-polyol mannitol were observed to rise dramatically in the biotrophic interaction of the rust fungus Uromyces fabae and its host plant Vicia faba. Mannitol was found in millimolar concentrations in extracts and apoplastic fluids of infected leaves and also in extracts of spores. We suggest that this polyol might have at least a dual function: first, as a carbohydrate storage compound, and second, as a scavenger of reactive oxygen species. Mannitol accumulation is accompanied by high expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
132
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(147 citation statements)
references
References 47 publications
(72 reference statements)
14
132
0
1
Order By: Relevance
“…All four polyols have been detected in some Aspergillus species (Beever & Laracy, 1986;Nesci et al, 2004) and in C. sake (Abadias et al, 2000). In addition to their use as compatible solutes, polyols can also serve as carbon storage compounds, they may help in balancing the cellular redox potential (Diano et al, 2006), and they can act as scavengers of reactive oxygen species (Voegele et al, 2005). At optimal growth salinity, H. werneckii accumulated a mix of polyols with different lengths of carbon backbone (from three to six atoms) in various ratios.…”
Section: Discussionmentioning
confidence: 99%
“…All four polyols have been detected in some Aspergillus species (Beever & Laracy, 1986;Nesci et al, 2004) and in C. sake (Abadias et al, 2000). In addition to their use as compatible solutes, polyols can also serve as carbon storage compounds, they may help in balancing the cellular redox potential (Diano et al, 2006), and they can act as scavengers of reactive oxygen species (Voegele et al, 2005). At optimal growth salinity, H. werneckii accumulated a mix of polyols with different lengths of carbon backbone (from three to six atoms) in various ratios.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the vast ecological host ranges of even individual isolates of generalist pathogens like B. cinerea do not readily fit into the assumptions of this mechanistic model, as this pathogen can simply evade any new resistance mechanism by moving to another equally suitable plant host. While some molecules, such as chitin and mannitol, can trigger PTI to provide resistance against generalist fungi, it is not fully understood how generalist pathogens fit into the intricate host/pathogen coevolution assumption foundational to ETI/PTI (Voegele et al, 2005;Staal et al, 2008;Stergiopoulos and de Wit, 2009;Liu et al, 2012;Meena et al, 2015;Patel and Williamson, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Polyol accumulation during infection has also been reported in cucumber and sunflower (Abood and Losel, 2003;Jobic et al, 2007). Voegele et al (2005) reported that mannitol accumulation in broad bean after fungal infection is due to fungal mannitol dehydrogenase, which could be related to carbon storage for the fungal pathogen and scavenging of reactive oxygen species (ROS), which are important in plant defense reactions. Because broad bean does not normally synthesize and use mannitol, this strategy of the fungal pathogen could be effective for pathogenicity.…”
Section: Polyols In Pathogenicitymentioning
confidence: 99%